Digital Detox and Gandhian Simplicity: A Voluntary Consumption Reduction in the Age of Social Media Addiction - Daksh (Academia Journal of Humanities & Social Sciences, 2026)
The modern economy of attention marked by the social media produces the compulsive engagement and consumption, signalling to elevate a political-ethical issue; one that is concerned with autonomy and not just with the personal wellbeing. In this paper, the digital detox through the concept of Gandhian simplicity particularly Aparigraha (non-possession), Swaraj (self-rule), and ethical self-restraint has been analysed, considering the voluntary reduction of digital engagement as a consumption restraint. To address this issue, the paper has employed the qualitative synthesis of the literature, using a critical review of existing interdisciplinary literature on the issue of problematic use of technology and interpretive textual analysis of Gandhian writings, which are combined to contextualise the urgency and the scale. The paper redefines the digital detox as maintaining the ethical forms of self-management in an algorithmically mediated space, instead of self-optimisation that aims at productivity. It further develops a normatively based, vows based paradigm of digital restraint that has the implications for the political ethics, digital citizenship, and platform governance.